Fullerene C60 protects against 7,12-dimethylbenz [a] anthracene (DMBA) induced-pancreatic damage via NF-?B and Nrf-2/HO-1 axis in rats - Beyaz, Seda; Aslan, Abdullah; Gok, Ozlem; Ozercan, Ibrahim Hanifi; Agca, Can Ali (Oxford Univ Press, 2023)
The objective of this investigation was to investigate the protective effects of fullerene C-60 nanoparticle against pancreatic damage experimentally induced by 7,12-dimethylbenz [a] anthracene (DMBA) in female rats. Fullerene C-60 nanoparticle was administered to rats 5 times a week by oral gavage (o.g) at 1.7 mg/kg bw 7 days after DMBA administration. 60 Wistar albino female rats divided to four groups; Groups: (1) Control group: Fed with standard diet; (2) Fullerene C-60 group: Fullerene C-60 (1.7 mg/kg bw); (3) DMBA group: DMBA (45 mg/kg bw); (4) Fullerene C-60 + DMBA group: Fullerene C-60 (1.7 mg/kg bw) and DMBA (45 mg/kg bw). Lipid peroxidation malondialdehyde (MDA), catalase activity (CAT) and glutathione (GSH) levels in pancreatic tissue were determined by spectrophotometer. Protein expression levels of p53, HO-1, p38-alpha (MAPK), Nrf-2, NF-kappa B and COX-2 in pancreatic tissue were determined by western blotting technique. In our findings, compared to the group given DMBA, MDA levels and p38-alpha, NF-kappa B and COX-2 levels decreased, CAT activity, GSH level, total protein density and p53, HO-1, Nrf-2 levels in the groups given fullerene C-60 nanoparticle an increase in expression levels was observed. Our results showed that fullerene C-60 nanoparticle may be more beneficial in preventing pancreatic damage. [GRAPHICS] .
Keywords: DMBA; fullerene C60; Nrf-2; oxidative stress; pancreatic damage